Effect of Waste Polymer Modified Bitumen with Milled Corn Cob as a Partial Replacement for Filler in Asphaltic Concrete (2020)
There is need to consider the use of cheaper and locally available materials so as to minimize the construction cost for sustainable development. Therefore, this research evaluated the physical and mechanical properties of waste plastic bottles modified bitumen with Milled Corn Cob (MCC) as a partial replacement for filler. Waste polymer was obtained from different waste generation points. A portable gas cooker was used to melt the waste polymer. Corn cob was sun-dried, and milled by an abrasion machine. Also, 60/70 penetration grade of bitumen was used for the study. The bitumen was replaced by waste polymer of 5%, 10%, and 15%. Bitumen modified samples were further prepared by mixing it with MCC of 10%, 30%, and 50%. Penetration, softening point, ductility, viscosity, flash point, fire point, loss on heating, specific gravity, stability, and flow were carried out on unmodified, modified bitumen and asphalt samples. All tests were conducted in accordance with the method of testing established by Indian Standard (IS) specification. Penetration, ductility, viscosity, flash point, fire point values decreases with increase in waste polymer content while softening point and loss on heating increases with increase in waste polymer content. Stability and flow value decreases with an increase in waste polymer and MCC content. The Optimum bitumen content, stability, and flow values for all the samples conform to the acceptable limits specified by Federal Ministry of Works (FMW) (1997) and IS specification. The results indicated an improvement in shear resistance, increment in resistance to deformation and optimum modifier content was found to be 10% for waste polymer and MCC.